A descriptive study of reportable gastrointestinal illnesses in Ontario, Canada, from 2007 to 2009 - Vrbova Linda; Johnson Karen; Whitfield Yvonne; Middleton Dean (BMC, 2012)
Abstract Background Gastrointestinal illnesses (GI) continue to pose a substantial burden in terms of morbidity and economic impact in Canada. We describe the epidemiology of reportable GI in Ontario by characterizing the incidence of each reportable GI, as well as associated demographics, clinical outcomes, seasonality, risk settings, and likely sources of infection. Methods Reports on laboratory confirmed cases of amebiasis, botulism, campylobacteriosis, cryptosporidiosis, cyclosporiasis, giardiasis, hepatitis A, listeriosis, paratyphoid fever, salmonellosis, shigellosis, typhoid fever, illness due to verotoxin-producing Escherichia coli (VTEC-illness), and yersiniosis, from January 1, 2007 to December 31, 2009 were obtained from Ontario's passive reportable disease surveillance system. Cases were classified by history of relevant travel, association with outbreaks, and likely source of infection, obtained through follow-up of reported cases by local health authorities. Results There were 29,897 GI reported by health authorities in Ontario from 2007 to 2009. The most frequently reported diseases were campylobacteriosis (10,916 cases or 36.5% of all GI illnesses) and salmonellosis (7,514 cases, 25.1%). Overall, 26.9% of GI cases reported travel outside of Ontario during the relevant incubation period. Children four years of age and younger had the highest incidence rate for most GI, and significantly more (54.8%, p<0.001) cases occurred among males than females. The most commonly reported sources of infections were food (54.2%), animals (19.8%), and contact with ill persons (16.9%). Private homes (45.5%) and food premises (29.7%) were the most commonly reported exposure settings. Domestic cases of campylobacteriosis, cryptosporidiosis, giardiasis, salmonellosis, and VTEC-illness showed seasonal patterns with incidence peaking in the summer months. Conclusions Reportable GI continues to be a burden in Ontario. Since more than one in four GI cases experienced in Ontario were acquired outside of the province, international travel is an important risk factor for most GI. Because private homes are the most commonly reported risk settings and the main suspect sources of infection are food, animal contact and ill persons, these findings support the continued need for public health food safety programs, public education on safe handling of food and animals, and proper hand hygiene practices.